IoT Board Education Design and Analysis for Elementary School Students - Ariyanto, Rudy; Rohadi, Erfan; Fahrur Rozi, Imam; Al Hadid Firdaus, Vipkas; Noprianto, ‎; Wakhidah, Rokhimatul; Arianto, Rakhmat; Puspa Kirana, Annisa; Nurhasan, Usman; Prastiyo, Sugeng (KnE Social Sciences, 2024)
This study aimed to design and analyse IoT board education for elementary school students as a supporting tool for learning Programming Logic. The Programming Logic Learning curriculum was implemented in elementary schools to develop students’ critical thinking. The study used the waterfall method through the following phases: system analysis and requirements, design, development, testing, and implementation. In the performance system test, a trial was done for elementary school students, and a User Acceptance Test (UAT) was done for the Programming Logic subjects. The results of the Black Box Testing showed that all features could run well. Trials of several elementary school students showed that 80% of students were able to use it well and were interested in the IoT board education and UAT testing of The Guardian Teacher, which showed 100% suitability to the needs. In conclusion, the IoT Board Education System can be implemented in Elementary Schools to achieve Programming Logic purposes. Keywords: IoT, programing logic learning, board education, needs analysis